2004
DOI: 10.1002/eat.10244
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of severe anorexia nervosa in Switzerland: 40 years of development

Abstract: The incidence of severe anorexia nervosa in the canton of Zurich rose significantly during the 1960s and 1970s. Since then, the incidence appears to have reached a plateau.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 17 publications
0
30
1
5
Order By: Relevance
“…A study covering four decades was published by Milos et al (2004) describing a significant increase in the admitted incidence of severe AN during the 1960s and 1970s in a Swiss region. Hsu's review (1996) of literature published in the period 1985-1995, including case register studies, two stage studies, population studies and longitudinal studies, covering a 1935-1991 time span, concluded an increasing trend.…”
Section: Introductionmentioning
confidence: 99%
“…A study covering four decades was published by Milos et al (2004) describing a significant increase in the admitted incidence of severe AN during the 1960s and 1970s in a Swiss region. Hsu's review (1996) of literature published in the period 1985-1995, including case register studies, two stage studies, population studies and longitudinal studies, covering a 1935-1991 time span, concluded an increasing trend.…”
Section: Introductionmentioning
confidence: 99%
“…The answers to these questions are approached using long-term studies (Lucas et al, 1999;Milos et al, 2004) and meta-analyses (Hoek, 2006;Hoek & van Hoeken, 2003;Hsu, 1996). These authors observed that the incidence of AN increased significantly during the 1960s and 1970s in females 12-to 25-years-old, despite not registering at epidemic proportions.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have suggested an increased prevalence of AN during the second half of the 20 th century Hoek & Van Hoeken, 2003;Preti et al, 2009). However, this increase has not been reflected in an increase in the number of cases of AN in hospital records (Milos et al, 2004). This may mean that while the majority of cases are not seeking treatment and are likely the less severe cases of AN.…”
Section: Resultsmentioning
confidence: 99%
“…Die Inzidenz der Anorexia nervosa stieg bis Ende der 70er Jahre des letzten Jahrhunderts an und ist seither ungefähr konstant. Bei der Prävalenz der Bulimia nervosa konnte ein Anstieg bis in die 1990er Jahre hin beobachtet werden ( [41], Übersicht bei [42] Untersuchte Veränderungen in den Hirnstrukturen und der Hirnfunktion bei Anorexia nervosa mit Untergewicht sind Vergrösserungen der Ventrikel und Defizite sowohl in der grauen als auch der weissen Substanz sowie Änderun-gen des zerebralen Blutflusses. Diese sind gemäss der Zusammenfassung von Kerem et al [45] bei Gewichtsrestitution grösstenteils reversibel, wobei in den meisten Studien nach Genesung kleine Defizite bestehen bleiben [46].…”
Section: Epidemiologieunclassified